2019
DOI: 10.5539/jas.v11n10p29
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Sows’ Reproductive Performance in Different Parities and Lifetime Productivity in Spain

Abstract: Our objective was to characterize use of nurse sows in Spanish breeding herds. We analyzed 466 111 parity records and lifetime records of 92 716 sows farrowed between 2011 and 2017 in 69 herds having nurse records. Nurse sows were defined as sows that had weaned 2 or 3 litters in the same lactation period. Mixed-effects models were applied to the data to compare reproductive performance and lifetime productivity between nurse and non-nurse sows. Of all the sows, 6 705 (7.2%) sows served as nurse sows at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…While the use of foster-in and nurse-sow techniques can increase the number of PW and produce heavier litter weights at weaning, it could decrease the foster or nurse sow’s post weaning reproductive performance due to increased loss of body reserves and impaired metabolic state in the lactating sow [ 22 , 49 ]. However, it has been found that nurse sows had farrowing rates and PBA similar to non-nurse sows in any parity, and the only difference was that they had a prolonged weaning-to-first-mating interval [ 50 ]. Consequently, the nurse sows produced 3–7 more herd-life annualized PW than non-nurse sows.…”
Section: Reviewmentioning
confidence: 99%
“…While the use of foster-in and nurse-sow techniques can increase the number of PW and produce heavier litter weights at weaning, it could decrease the foster or nurse sow’s post weaning reproductive performance due to increased loss of body reserves and impaired metabolic state in the lactating sow [ 22 , 49 ]. However, it has been found that nurse sows had farrowing rates and PBA similar to non-nurse sows in any parity, and the only difference was that they had a prolonged weaning-to-first-mating interval [ 50 ]. Consequently, the nurse sows produced 3–7 more herd-life annualized PW than non-nurse sows.…”
Section: Reviewmentioning
confidence: 99%
“…The proportion of sows inseminated 0–3 days postweaning were significantly higher for nurse sows in fifth and sixth parity when compared with nonnurse sows. Similarly, the proportion of sows inseminated 7–20 days postweaning was significantly higher for second, third, fifth, and sixth parity nurse sows when compared with nonnurse sows (Iida et al, 2019). These findings are most likely caused by lactational oestrus, as nurse sows are typically selected with focus on sow body condition but also appetite, and thus, the subsequent reproduction of these sows will not be compromised when being selected as nurse sows, and these facts may influence on results when analyzing retrospective data.…”
Section: Potential Risks When Increasing the Length Of The Lactation ...mentioning
confidence: 98%
“…This study revealed that 7.2% of the sows were used as nurse sows at least once in their lifetime. Being used as a nurse sow increased the lactation period with on average 9.1 days, but the farrowing rate in the subsequent litter did not differ between nurse sows and nonnurse sows (Iida et al, 2019). The proportion of sows inseminated 0–3 days postweaning were significantly higher for nurse sows in fifth and sixth parity when compared with nonnurse sows.…”
Section: Potential Risks When Increasing the Length Of The Lactation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…With a fertilization rate close to 90% [4], the number of early embryos can potentially reach 18-27. However, at farrowing, litter size is reduced to 9-13 piglets per sow due to the influence of many factors [5,6]. One factor we must emphasize is the spontaneous conceptus loss.…”
Section: Introductionmentioning
confidence: 99%